Prognostic relevance of exercise pulmonary hypertension: results of the multicentre PEX-NET Clinical Research Collaboration - Kovacs, Gabor; Humbert, Marc; Avian, Alexander; Lewis, Gregory D.; Ulrich, Silvia; Noordegraaf, Anton Vonk; Souza, Rogerio; Galiè, Nazzareno; Malhotra, Rajeev; Saxer, Stephanie; Grünig, Ekkehard; Egenlauf, Benjamin; et al. (The European respiratory journal, 2024)
Background: Exercise pulmonary hypertension (PH) was defined by a mean pulmonary arterial pressure (mPAP)/cardiac output (CO) slope >3 mmHg·min·L−1 between rest and exercise in the 2022 European Society of Cardiology/European Respiratory Society PH guidelines. However, large, multicentre studies on the prognostic relevance of exercise haemodynamics and its added value to resting haemodynamics are missing. Patients and methods: The PEX-NET (Pulmonary Haemodynamics during Exercise Network) registry enrolled patients who underwent clinically indicated right heart catheterisations both at rest and ergometer exercise from 23 PH centres worldwide. In this retrospective analysis we included subjects with resting mPAP <25 mmHg and complete haemodynamic data at rest and exercise in the same body position. Mixed effects Cox proportional hazard models with random effect centre were applied to identify independent markers of prognosis among the haemodynamic parameters. Results: We included 764 patients (64% females; median (interquartile range) age 59 (46-69) years and mPAP 17 (14-20) mmHg). Median (range) observation time was 6.8 (0.1-15.9) years and 87 patients (11%) died during follow-up. After adjustment for age, sex, haemoglobin level and resting haemodynamics, CO (hazard ratio (HR) 0.85, 95% CI 0.77-0.93; p=0.001) and transpulmonary gradient (HR 1.04, 95% CI 1.00-1.08; p=0.044) at peak exercise and the mPAP/CO slope (HR 1.12, 95% CI 1.06-1.18; p<0.001) were the only independent predictors of prognosis. Patients with a mPAP/CO slope >3 mmHg·min·L−1 had significantly worse survival compared to those with a mPAP/CO slope ≤3 mmHg·min·L−1 (HR 2.04, 95% CI 1.16-3.58; p=0.013). Conclusion: The mPAP/CO slope is a robust and independent predictor of prognosis in patients with normal or mildly elevated resting PAP that provides prognostic information beyond resting haemodynamics and appears suitable to define exercise PH.